Chemical constituents and bioactivities of hops (Humulus lupulus L.) and their effects on beer‐related microorganisms. (23rd February 2022) - Sun, Shaokang; Wang, Xiaochen; Yuan, Ai; Liu, Jianlin; Li, Zebin; Xie, Dongxiao; Zhang, Huimin; Luo, Wenqing; Xu, Hengyuan; Liu, Jinshang; Nie, Cong; Zhang, Haojun
Abstract: The female inflorescence of hops is traditionally used in the brewing industry to impart bitterness, aroma, flavour and longer shelf life to beer, where the bittering acids are the main compounds that enhance the quality of the beer. In recent years, a wide variety of bioactive compounds have been reported to be present in female flowers. Due to the growing consumer interests in natural ingredients, a great deal of research has been carried out in the last few years to find new sources of functional biomolecules. This paper reviews the recent applications of hops in the food, pharmaceutical and cosmetic industries and provides an overview of the bioactive potential of hops. In addition, the analytical techniques of hops compound are reviewed. The biological activities of hops compound such as antibacterial, antifungal, cardioprotective, antioxidant, anti‐inflammatory and anticancer are reviewed and the recent effects of hop bittering derivatives on beer‐related microbial activity are also presented. It is thus clear that hops have a high potential as bioactive components for use as preservatives in fresh foods to extend shelf life and as cosmetic formulations for skin care products as well as nutraceutical and health implications. Abstract : The female inflorescence of hops is recognised in the brewing industry as a bittering agent and is traditionally used in the brewing industry to impart bitterness, aroma, flavour and longer shelf life to beer, where the bittering acid is the main compound that en‐hances the quality of the beer. The biological activities of hops extracts such as antibacterial, antifungal, cardioprotective, antioxidant, anti‐inflammatory and anticancer are reviewed and the recent effects of hops and their derivatives on beer‐related microbial activity are presented.